Scavengers As an Alternative Waste Management Project: a Study On The Civil Society of Kiringan Village in Sustainable Development Goals 15 through 3R Waste Management - Saputra, Hendra Lana; Noormansyah, Reza (POPULIKA, 2024)
This research aims to determine the role of scavengers in Kiringan Village, Magelang City, within the framework of civil society concerning their livelihoods, namely managing and recycling waste, which contributes to Sustainable Development Goals (SDGs) 15. Waste itself has become a national problem, with the volume of garbage reaching 35,000. Ninety-three million tons in 2022 can be broken down further, with Central Java Province coming at 5.76 million tons and Magelang City at 80.51 tons per day. This condition becomes problematic amidst demands regarding the universal norm SDG 15, namely "Protecting terrestrial ecosystems". The role of scavengers is a concrete alternative solution in solving this problem. The role of scavengers will be reviewed using Tocqueville's conception of civil society, namely an organized area of ​​social life characterized by voluntary, self-generating, and self-supporting, which is synthesized with SDGs 15, namely waste management and recycling through 3R (reuse, reduce, recycle). Interpretive analysis of field and literature studies examines and draws conclusions from research findings. The 3R activities of scavengers make waste manageable and can mitigate the waste volume. With volunteerism, self-sufficiency, and self-sufficiency, reuse activities are carried out by reusing used plastic bottles, reducing by collecting plastic waste in village areas, and recycling through the implementation of training from the Sandal Flip-flops Community so that the scavenger community can produce handicrafts from recycled waste—plastic bottles. Waste management by the scavengers of Kiringan Village has an essential role in protecting the land ecosystem from garbage. Keywords: Civil Society; Kampung Kiringan’s Scavengers; Sustainable Development Goals; Waste Management.